Assembly of protein complexes restricts diffusion of Wnt3a proteins. (December 2018) - Takada, Ritsuko; Mii, Yusuke; Krayukhina, Elena; Maruyama, Yuusuke; Mio, Kazuhiro; Sasaki, Yoshikazu; Shinkawa, Takao; Pack, Chan-Gi; Sako, Yasushi; Sato, Chikara; Uchiyama, Susumu; Takada, Shinji
Abstract Members of the Wnt protein family play roles in many aspects of embryogenesis and homeostasis. Despite their biological significance, characteristics of Wnt proteins still remain unclear, mainly due to their insolubility after the removal of serum. Here we examine Wnt proteins in serum-containing media by using analytical ultracentrifugation with a fluorescence detection system. This analysis reveals that Wnt3a assembles into high-molecular-weight complexes that become dissociable by interaction with the extracellular domain of the Frizzled8 receptor or secreted Wnt-binding protein sFRP2. Cross-linking and single-particle analyses of Wnt3a fractionated by gel filtration chromatography show the homo-trimer to be the smallest form of the assembled Wnt3a complexes. Fluorescence correlation spectroscopy and immunohistochemistry reveal that the assembly of Wnt3a complexes restricted their diffusion and signaling range inXenopus laevis embryos. Thus, we propose that the Wnt diffusion range can be controlled by a balance between the assembly of Wnt complexes and their dissociation. Ritsuko Takada et al. show that Wnt3a assembles into high molecular weight complexes that restrict the diffusion of Wnt withinXenopus embryos. These results suggest that Wnt diffusion in cells is controlled by a balance between higher order complex assembly and dissociation by Wnt-binding proteins.